جودة الأداء الوظيفي وعلاقته بمستوى الرقابة الإدارية - بيات، صابرة; مشارة، فاطمة الزهرة (University Of Eloued جامعة الوادي, 2024)
.تهدف هذه الدراسة إلى معرفة جودة الأداء الوظيفي وعلاقته بمستوى الرقابة، وهذا من خلال وجهة نظر العاملين ببلدية قمار، حيث نبحث في إمكانية وجود علاقة بين جودة الاداء الوظيفي ومستوى الرقابة الادارية. اعتمدنا في هذه الدارسة على المنهج الوصفي، أما فيما يتعلق بأداة جمع البيانات تم استخدام أداة الاستبيان الذي تضمن 37 سؤالا مقسما على ستة أبعاد. لقد تم إجراء الدراسة الميدانية على عينة تتكون من 129 عامل بطريقة غير عشوائية حصصية على بعض العمال ببلدية قمار ولاية الوادي من مجتمع بحث مقدر بـ 643 مفردة. وبعد هذه الدراسة توصلنا إلى النتائج التالية: 1- توجد علاقة ارتباطية ذات دلالة احصائية بين المعرفة بالمتطلبات الوظيفية ومستوى الرقابة الادارية لدى العاملين ببلدية قمار ولاية الوادي. 2- توجد علاقة ارتباطية ذات دلالة احصائية بين كمية وجودة العمل المنجز ومستوى الرقابة الادارية لدى العاملين ببلدية قمار ولاية الوادي. 3- توجد علاقة ارتباطية ذات دلالة احصائية بين الابداع والابتكار ومستوى الرقابة الادارية لدى العاملين ببلدية قمار ولاية الوادي. 4- توجد علاقة ارتباطية ذات دلالة احصائية بين جودة الاداء الوظيفي ومستوى الرقابة الوقائية لدى العاملين ببلدية قمار ولاية الوادي. 5- توجد علاقة ارتباطية ذات دلالة احصائية بين جودة الاداء الوظيفي ومستوى الرقابة المتزامنة لدى العاملين ببلدية قمار ولاية الوادي. 6- توجد علاقة ارتباطية ذات دلالة احصائية بين جودة الاداء الوظيفي ومستوى الرقابة اللاحقة لدى العاملين ببلدية قمار ولاية الوادي. 7- توجد علاقة ارتباطية ذات دلالة احصائية بين جودة الاداء الوظيفي ومستوى الرقابة الادارية لدى العاملين ببلدية قمار ولاية الوادي. This study aims to know the quality of job performance and its relationship to the level of control, and this is from the point of view of the workers in the municipality of Ghomar, where we are looking into the possibility of a relationship between the quality of job performance and the level of administrative control. In this study, we relied on the descriptive approach, and as for the data collection tool, the questionnaire tool was used, which included 37 questions divided into six dimensions. The field study was conducted on a sample of 129 workers in a non-random, quota-based manner on some workers in the municipality of Ghomar, El Oued Province, from a research community estimated at 643 individuals. After this study, we reached the following results: 1- There is a statistically significant correlation between knowledge of job requirements and the level of administrative control among workers in the municipality of Ghomar, El Oued Province. 2- There is a statistically significant correlation between the quantity and quality of work accomplished and the level of administrative control among workers in the municipality of Ghomar, El Oued Province. 3- There is a statistically significant correlation between creativity and innovation and the level of administrative control among employees in the municipality of Ghomar, El Oued Province. 4- There is a statistically significant correlation between the quality of job performance and the level of preventive control among employees in the municipality of Ghomar, El Oued Province. 5- There is a statistically significant correlation between the quality of job performance and the level of simultaneous control among employees in the municipality of Ghomar, El Oued Province. 6- There is a statistically significant correlation between the quality of job performance and the level of subsequent control among employees in the municipality of Ghomar, El Oued Province. 7- There is a statistically significant correlation between the quality of job performance and the level of administrative control among employees in the municipality of Ghomar, El Oued Province.
دراسة ميدانية على عينة من عمال بلدية قمار ولاية الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: الأداء الوظيفي; Job performance; الرقابة الإدارية; Administrative control